2005
DOI: 10.1002/aoc.863
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of polyoctenamer with WCl6eAlCH2Cl2 catalyst system via ring‐opening metathesis polymerization

Abstract: A typical low-strain monomer, cyclooctene, was polymerized via ring-opening metathesis polymerization with electrochemically produced active species. The structural properties of the polyoctenamer were determined by NMR, gel-permeation chromatography and differential scanning calorimetry. Analysis of the polyoctenamer microstructure by 1 H and 13 C NMR spectroscopy indicates that the polymer contains a highly cis stereoconfiguration of the double bonds (σ c = 0.75). The resulting polymer is of low molecular we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0

Year Published

2005
2005
2009
2009

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 17 publications
(10 reference statements)
3
6
0
Order By: Relevance
“…Linear PCO, synthesized using catalyst 1 according to the optimal conditions using THF and PPh 3 , contained 56% cis olefin and exhibited a T m of 10 °C, which is in good agreement with published experimental values 32,33. Hydrogenation of PCO (Entry 18) was conducted by treatment of the polymer with tosyl hydrazide and tripropyl amine in xylenes9,3438 and yielded linear, narrowly dispersed HDPE.…”
Section: Synthesis Of Linear High Density Polyethylenesupporting
confidence: 84%
“…Linear PCO, synthesized using catalyst 1 according to the optimal conditions using THF and PPh 3 , contained 56% cis olefin and exhibited a T m of 10 °C, which is in good agreement with published experimental values 32,33. Hydrogenation of PCO (Entry 18) was conducted by treatment of the polymer with tosyl hydrazide and tripropyl amine in xylenes9,3438 and yielded linear, narrowly dispersed HDPE.…”
Section: Synthesis Of Linear High Density Polyethylenesupporting
confidence: 84%
“…The monomer COC has been homopolymerized previously by ROMP techniques, yielding a polyoctenamer. 15 (1) Table 1 summarizes the results obtained from the homopolymerization and copolymerization of CPE and COC under the same conditions. The glass transition temperatures T g of polypentenamer and poly(CPE-co-COC) are −20.8 • C and −18.7 • C respectively.…”
Section: Resultsmentioning
confidence: 99%
“…2,3 A detailed 13 C NMR study of the polyoctenamer was previously reported. 15 In copolymers of the two monomers, M 1 (CPE) and M 2 (COC), the compositional dyads may be M 1 M 1 , M 1 M 2 , M 2 M 1 or M 2 M 2 (Scheme 2). The structural evidence of copolymerization lies in a detailed NMR analysis of poly(CPE-co-COC), which is additive for the homopolymer.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…9 -11 A WCl 6 -Al-CH 2 Cl 2 catalyst system that has been electrochemically reduced brings about the metathesis of α-and β-olefins, as well as the cross-metathesis of non-functionalized olefins 12,13 and the ADMET polymerization of 1,9-decadiene 14,15 , with good activity and selectivity. The electrochemical generation apparently stabilizes the higher oxidation state of the active species responsible for the metathesis reaction, resulting in a high selectivity.…”
Section: Introductionmentioning
confidence: 99%